2022
DOI: 10.46827/ejmms.v7i4.1289
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Factors Influencing the Job Motivation of Public Sector Health Care Workers in Nakuru County, Kenya

Abstract: Diverse factors provide indicators of job motivation challenges amongst healthcare workers. These factors include the high level of employee turnover. For example, in 2017, an estimated 700 doctors quit employment in government-run hospitals. Additionally, the Kenya Medical Practitioners and Dentist Union (KMPDU) estimated that up to 2,300 doctors had left devolved sector employment between 2014 and 2016 for private sector engagement or further education abroad. Moreover, the various groups of healthcare worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(30 reference statements)
0
1
0
1
Order By: Relevance
“…Motivation plays a vital role in increasing the desire and enthusiasm of nurses to quickly complete their tasks correctly (Blegur and Amalia, 2019) so that when nurses have high work motivation, their performance will increase. Idiegbeyan-Ose research (Idiegbeyan-Ose et al, 2019) and (Githatu, 2022) confirmed that motivation significantly positively affects nurse job satisfaction. Based on this description, the hypothesis is formulated as follows:…”
Section: Theoretical Reviewmentioning
confidence: 92%
“…Motivation plays a vital role in increasing the desire and enthusiasm of nurses to quickly complete their tasks correctly (Blegur and Amalia, 2019) so that when nurses have high work motivation, their performance will increase. Idiegbeyan-Ose research (Idiegbeyan-Ose et al, 2019) and (Githatu, 2022) confirmed that motivation significantly positively affects nurse job satisfaction. Based on this description, the hypothesis is formulated as follows:…”
Section: Theoretical Reviewmentioning
confidence: 92%
“…Idiegbeyan-Ose et al (2019) danGithatu (2022) menegaskan bahwa motivasi berpengaruh positif dan signifikan terhadap kepuasan kerja Yunardi et. al.…”
unclassified